(untitled) (Лучшие интеллектуальные исследования, 2024)
This article investigates the intricate relationship between grammatical structures and language evolution. Focusing on the principles of linguistic change, we examine how alterations in grammatical features—such as word order, inflectional morphology, and syntactic constructions—contribute to broader language evolution. We analyze examples from diverse language families, demonstrating how internal and external factors interact to shape grammatical change and its impact on the overall linguistic system.